2009
DOI: 10.1177/1534484309356059
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Literature Review: Performance Interventions That Assist Chinese Expatriates’ Adjustment and Performance: Toward a Conceptual Approach

Abstract: China continues to rapidly grow globally. As China’s global presence continues to grow, the use of Chinese expatriates around the world will seemingly grow as well. However, little attention is paid to Chinese multinational corporations and their use of expatriates in the literature, while a growing collection of literature focusing on Western expatriates exists. This is a conceptual article that examines the extant literature on any performance interventions designed to improve the adjustment and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Other research on the topic steered away from the linear relationship between organizational factors and adjustment success, and chose to address the complicated nature of expatriation. This body of research took into consideration issues such as societal gender assumptions and their impact on different organizational treatment of men and women expatriates (Cooke ; Shortland ), the moderating roles of foreign subsidiary support and cultural distance to expatriate effectiveness (Chen, Kirkman and Kim ), and cultural impact on the kind of organizational expatriate training desired and provided (Li and Hugh ; Wood and Mansour ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other research on the topic steered away from the linear relationship between organizational factors and adjustment success, and chose to address the complicated nature of expatriation. This body of research took into consideration issues such as societal gender assumptions and their impact on different organizational treatment of men and women expatriates (Cooke ; Shortland ), the moderating roles of foreign subsidiary support and cultural distance to expatriate effectiveness (Chen, Kirkman and Kim ), and cultural impact on the kind of organizational expatriate training desired and provided (Li and Hugh ; Wood and Mansour ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of research on expatriation focuses on the experiences of Western expatriates. It has been suggested that non-Western expatriates will also face challenges in adapting to unfamiliar contexts and the majority relocate to Western, industrialised countries, rather than other developing countries (Wood and El Mansour 2010). The following section therefore questions the literature on expatriation from the Korean perspective by reference to Korea's cultural values.…”
Section: Korea and Expatriationmentioning
confidence: 99%
“…The IA field is still largely an unknown territory, especially concerning expatriate experiences. A review by Wood and Mansour (), for example, found only 14 articles published on Chinese expatriates between 1996 and 2007. Much of the recent research concerns issues such as cross‐cultural training (Zhang and Fan ), IA adjustment (Wang, Freeman and Zhu ) and performance management (Shen and Jiang ).…”
Section: Individual Motives and The Potential Significance Of Confucimentioning
confidence: 99%